Promotion and Tenure: Institution, Program, and Faculty-Candidate Characteristics - Peterson, Cathryn A.; Stuart, Daryl W.; Hargis, Jace; Patel, Rajul A. (Journal of physical therapy education, 2009)
Physical therapist education has long been a professional degree program, the primary emphasis of which has been placed upon teaching, service, and clinical practice. The purpose of this study was to characterize the institutions and programs that employ physical therapist faculty candidates seeking promotion and/or tenure, while also describing the faculty candidates themselves; and to determine if significant relationships exist between various institution/program- or faculty-specific characteristics and achieving success during the promotion and tenure review process. The sampling frame was the list of 199 accredited physical therapist education programs in the United States provided by CAPTE in July 2005. Department chairs were asked to complete an electronic survey, which contained 15 institutional and programspecific demographic questions, and 10 items about each of the faculty candidates who were up for promotion and/or tenure during the specified 5-year period. The results of this study indicate that most faculty candidates who were evaluated for promotion and/or tenure during the study period were female, possessed an academic doctorate, were seeking their first promotion from assistant to associate professor, and were successful with their promotion. Successful candidates came from institutions that offered academic doctorates, had formalized mentoring in place, and had programs that required student participation in faculty-driven research projects. The findings of this study provide a unique glimpse into physical therapist faculty candidates up for promotion and tenure, their programs, and institutions. Knowing the characteristics of promotion and/ or tenure candidates, their programs, and institutions may be beneficial for all stakeholders. Moreover, factors that may predict success during promotion and tenure review enlighten both individual faculty members and academic administrators alike.